Supply Control Of Oil Filter Spareparts Using EOQ And Min-Max Methods Based On Sales Forecast (Case Study: PT Astra International Tbk Soekarno Hatta) - Arfemitha, Nurlia Asih; Supian, Sudradjat; Nahar, Julita (International Journal of Global Operations Research, 2024)
Planning and controlling product inventory is very important for a company to ensure demand is met and maximize profits from sales effectively and efficiently. In addition, inventory planning and control are carried out to prevent excess or shortage of inventory. This study aims to predict sales and calculate inventory control to overcome excess stock and increased inventory costs on oil filter spare parts. The forecasting method used is Holt's Double Exponential Smoothing method to determine the number of sales of the four types of oil filter spare parts in the future and overcome the problem of oil filter spare parts inventory using the EOQ and Min-Max methods. Based on the research results, the resulting forecasting is accurate and the EOQ method results in a lower total inventory cost than the Min-Max method.